Neglected tropical diseases in Brazilian children and adolescents: data analysis from 2009 to 2013 - Eduardo Brandão; Sebastián Romero; Maria Almerice Lopes da Silva; Fred Luciano Neves Santos (BMC, 2017)
Abstract Background Neglected tropical diseases (NTDs) prevail in conditions of poverty and contribute to the maintenance of social inequality. Out of the NTDs prioritized by the Brazilian Ministry of Health, four parasitic infections require mandatory notification: acute Chagas disease, leishmaniasis, malaria, and schistosomiasis. Data on the behaviour of these NTDs in the young population are currently limited. This study seeks to analyse the epidemiological aspects of these parasitic infections in children and adolescents in Brazil. Methods A retrospective exploratory ecological study was conducted. A spatial analysis of the cases reported between 2009 and 2013 in individuals aged between 0 and 19 years that were notified through the Health Notification Aggravation Information System (SINAN) was performed. Results In total, 64,567 cases of cutaneous and visceral leishmaniasis, malaria, schistosomiasis, and acute Chagas disease were recorded in the SINAN database, representing a rate of 20.15 cases per 100,000 inhabitants. The average age of the cases was 12.2 years and 62.32% were male. Four hundred and three deaths related to these obligatorily reported parasites were recorded, indicating a case fatality rate of 0.62%. Visceral leishmaniasis and acute Chagas disease had the highest rates of lethality. A heterogeneous spatial distribution of the studied parasites was observed. Conclusions The number of cases and the lethality rate described in this study show that these diseases still represent a serious problem for public health in Brazil. This points to the need to encourage new research and the reformulation of social, economic, and public health policies aimed at ensuring better health and living conditions for all individuals, especially those among the populations considered vulnerable, as is the case of the young.